Pharmacists in dispensing drugs (PharmDisp): protocol for a clinical trial to test the effectiveness of distance education in training pharmacists for dispensing drugs - Tiago Marques dos Reis; Camilo Molino Guidoni; André Oliveira Baldoni; Edmarlon Giroto; Paulo Roque Obreli Neto; Lorena Rocha Ayres; Leonardo Régis Leira Pereira (Universidade de São Paulo, 2018)
ABSTRACT Dispensing drug is a moment in which the pharmacist is able to analyze pharmacotherapy and contribute to its rational use. However, research has shown that some pharmacists lack adequate knowledge to perform this service. This study aims to describe a research protocol for a clinical trial to test the effectiveness of a distance learning program to train pharmacists in dispensing drugs. This is a protocol for an open diagnostic, non-randomized, single group clinical trial. A 12-week duration distance learning course was structured on the Moodle platform for training community pharmacists who are registered in the Regional Board of Pharmacy and work as employees or owners in Brazilian community pharmacies. The course curricula involves concepts and practice of dispensing drugs applied to the treatment of hypertension, diabetes mellitus, dyslipidemia and asthma. Pharmacists are divided randomly into groups, to which previously selected tutors give directions to the discussion and clarify questions. A validated questionnaire is being used before and after the course to measure participants' knowledge. Participant satisfaction with the course is also being measured. Pharmacists who work in the study headquarters municipality receive two visits from a mystery shopper, before and after the course, to evaluate their performance in dispensing drugs. The virtual platform and the content of the course material were evaluated by judges. The study has been approved by the Research Ethics Committee of the School of Pharmaceutical Sciences of Ribeirão Preto, University of São Paulo. The sample size was estimated to provide desired power for testing the significance of the difference between baseline-to-endpoint change scores. Information about the course is being released through channels such as social networks. The results will be submitted for publication in scientific journals, but information enabling the identification of the study subjects will be kept confidential. The trial has been registered in The Brazilian Clinical Trials Registry with number RBR7mbrp3 on January 15th, 2015.